1992
DOI: 10.1177/088610999200700106
|View full text |Cite
|
Sign up to set email alerts
|

Women's Content in Social Work Curricula: Separate but Equal?

Abstract: There has been an ongoing debate on whether content on women's issues should be taught in a separate course or integrated throughout the social work curriculum. This study of the knowledge and attitudes of 70 undergraduate social work majors found that all the students had similar attitudes toward women's rights and feminism, but those who had taken a separate course had greater knowledge of female biological processes and the social and historical forces that have affected women. Social work has long been kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Greater educational attainment often leads to greater levels of feminist activism for all citizens (Henderson-King & Stewart, 1999), with the effects of education being the strongest when classes directly focus on gender inequities (Duncan, 1999;Nelson et al, 2008). Among social work students, some studies contend that exposure to feminist content in classrooms fosters a greater commitment to feminist activism (Abram, Schmitz, Taylor, Tebb, & Bartlett, 2001;Black, 1994;Lincoln & Koeske, 1987;Munson & Hipp, 1998;Vinton, 1992), while other studies suggest that participation and completion of certain academic courses inspires many sorts of political activism (Butler & Coleman, 1997;Fahs, 2012;Morrison Van Voorhis & Hoestetter, 2006;Rocha, 2000;Van Soest, 1996). However, a few studies cautioned that finishing a course on oppression did not lead to higher advocacy intentions (Van Soest, 1996;Weiss & Kaufman, 2006) even while it may serve a clear consciousness-raising role (Fahs, 2012).…”
Section: They Can't: Income Educational Attainment and Gender Cleavmentioning
confidence: 99%
See 3 more Smart Citations
“…Greater educational attainment often leads to greater levels of feminist activism for all citizens (Henderson-King & Stewart, 1999), with the effects of education being the strongest when classes directly focus on gender inequities (Duncan, 1999;Nelson et al, 2008). Among social work students, some studies contend that exposure to feminist content in classrooms fosters a greater commitment to feminist activism (Abram, Schmitz, Taylor, Tebb, & Bartlett, 2001;Black, 1994;Lincoln & Koeske, 1987;Munson & Hipp, 1998;Vinton, 1992), while other studies suggest that participation and completion of certain academic courses inspires many sorts of political activism (Butler & Coleman, 1997;Fahs, 2012;Morrison Van Voorhis & Hoestetter, 2006;Rocha, 2000;Van Soest, 1996). However, a few studies cautioned that finishing a course on oppression did not lead to higher advocacy intentions (Van Soest, 1996;Weiss & Kaufman, 2006) even while it may serve a clear consciousness-raising role (Fahs, 2012).…”
Section: They Can't: Income Educational Attainment and Gender Cleavmentioning
confidence: 99%
“…Some studies have also found that men in social work were more likely to accept traditional gender roles (Black, 1994), less desiring of gender equality (Spivey, 2006), and more oblivious to male privilege than their female counterparts (Taylor, 1994). However, gender differences might be less pronounced among social workers because there may be a higher proportion of feminist-identified men in this profession (Han & Chun-Chung Chow, 2010;Ritter, 2008;Rocha, 2000;Vinton, 1992).…”
Section: They Can't: Income Educational Attainment and Gender Cleavmentioning
confidence: 99%
See 2 more Smart Citations
“…In the early 1990s, two important studies were conducted on gender-sensitive social work curricula (Knight, 1991;Vinton, 1992). Results from these studies indicated that, although progress has been made, much remains to be accomplished in achieving the intended educational JUDITH NORMAN is associate professor and BARBARA WHEELER is professor emeritus, Brigham Young University, Provo, UT.…”
mentioning
confidence: 99%